Il familiar compound ghost dell’artista - Boitani, Piero (Status Quaestionis, 2016)
The essay addresses the multifaceted identity of modern artists starting from an analysis of T.S. Eliot’s “Little Gidding”, which presents a “compound”, multi-voiced protagonist. The compound ghost of the artist is thus the result of a combination of different voices of world literary tradition, from Shakespeare to Milton, from Dante to Mallarmé, from Poe to Ezra Pound, culminating in Yeats. The Irish poet’s “Cuchulain Comforted” adds to the composite identity of Eliot’s ghost by enacting the ultimate transition from life to death and allowing the artist to find his own voice in the underworld.